Evaluasi Program Pencegahan Gizi Buruk melalui Promosi dan Pemantauan Pertumbuhan Anak Balita - Dudut Eko Juliawan, Yayi Suryo Prabandari, T. Ninuk S. Hartini (Berita Kedokteran Masyarakat (BKM), 2010)
Background: Recently, the infant mortality rate in West Nusa Tenggara is remaining high which is 77 per 1,000 birth lives. This number is above national rates (35 per 1,000 birth lives). The maternal mortality rate is also high, which is 370 per 100,000 births, and is above national rates 307 per 100,000 births. While the literate rate is still under national rate. Degree of community health that has been worse was worsening through outbreak malnutrition in 2005. Malnutrition can be prevented through posyandu activity. Growth monitoring and promotion of children under five years old in posyandu can detect case of malnutrition early.Objective: The study was aimed to know how execution of programmed of growth monitoring and promotion of children under five years old in  posyandu in Mataram municipality was undertaken.Method: This was a qualitative study. Forty eight informants participated in this study. Informants consisted of 14 mother of children under five years, 10 cadres, 5 leaders of community, 11 staff of community health centre (puskesmas), 7 members of Mataram  posyandu operational working group  (pokjanal posyandu) and 1 staff provincial health office. Location of the study was in Mataram municipality. Subjects were chosen purposively at three sub district that were Ampenan, Cakranegara and Mataram. Data were collected by in depth interview, focus group discussion and observation. Triangulation on methods and informants/source were used in assessing the trustworthiness of data. Data analysis was carried out through data transcript, open coding, axial coding,data presentation and making conclusion.Result: Mothers of children under five years old with low education and low income did not comprehend meaning growth of child, so they were unable to prevent malnutrition. Growth monitoring and promotion of children under five years old has not been carried out well, particulary at desk 3th (weighing measurement) and desk 4th (counseling). Cadres have not had capacity to detect malnutrition, that may caused by lack of training. Staff of  puskesmas had so much work so that they did not work properly in delivering  posyandu.Conclusion: Growth monitoring and promotion programmed of child under five years old has not been carried out well, low work performance of cadre and  puskesmas staff and lack of supervision.Keywords: malnutrition,  posyandu, growth monitoring, mother of children under five years old.